The Influence of Manufacturing Technology on the Structure and Properties of a Composite Based on EN AB-43000 Alloy Reinforced with SiC Particles - Łągiewka, M. (Archives of Foundry Engineering, 2026)
This paper presents an innovative and comprehensive comparison of the influence of various casting technologies and mould materials on the structure and mechanical properties of composites based on EN AB-43000 alloy reinforced with silicon carbide particles. The composite castings and castings of the matrix alloy were produced by gravity casting into conventional sand moulds, into shell moulds made using the Croning process, and into metal moulds. Particular attention was paid to composite castings produced using die-casting technology, the application of which in the case of metal composites reinforced with SiC particles poses a significant technological challenge due to the difficulties associated with achieving a homogeneous structure and the appropriate quality of the castings. The composite castings were produced with 10% and 15% SiC particle content. The cast strength specimens were tested for tensile strength, yield strength and elongation on a Zwick 1488 testing machine. In order to determine the influence of casting technology and mould material on the structure of the tested materials, microstructural photographs were taken of the samples remaining after the strength tests. The results of the tests show that the addition of silicon carbide to the matrix alloy causes a slight decrease in tensile strength (Rm), a significant decrease in elongation, but a slight increase in the yield strength (R02). The composites cast by gravity into moulds made from conventional moulding sand exhibited the greatest percentage increase in R0.2 and the smallest decrease in Rm compared to the matrix alloy. Die-castings made from both the pure matrix alloy and the composite exhibited the best properties. The structure of these composites was homogeneous, free from defects such as porosity, clusters or non-metallic inclusions. The research conducted demonstrated the relationship between the manufacturing technology, the homogeneity of the composite structure and the mechanical properties, which allowed die-casting to be identified as the most effective method for producing the composite materials under investigation.